'For God so loved the world...' The story of God's work on Earth according to Douglas John Hall - Conradie, Ernst M. (Scriptura, 2008)
his essay reconstructs the way in which Douglas John Hall tells the story of God's work. The argument of this essay is that Hall's entire theology could be described as an exposition of the famous formula in John 3:16, "for God so loved the world". His emphasis on a theology of the cross is explored with reference to the doctrines of creation, humanity, providence, redemption, the church and the eschatological consummation. It is argued that Hall's strength (his Christological focus on a theology of the cross) is also his weakness, given his underdeveloped pneumatology. It would therefore be important to further investigate Hall's understanding of the filioque problem.